2021
DOI: 10.1200/jco.20.02822
|View full text |Cite
|
Sign up to set email alerts
|

Pertuzumab Plus High-Dose Trastuzumab in Patients With Progressive Brain Metastases and HER2-Positive Metastatic Breast Cancer: Primary Analysis of a Phase II Study

Abstract: PURPOSE Effective therapies are needed for the treatment of patients with human epidermal growth factor receptor-2 (HER2)-positive metastatic breast cancer (MBC) with brain metastases. A trastuzumab radioisotope has been shown to localize in brain metastases of patients with HER2-positive MBC, and intracranial xenograft models have demonstrated a dose-dependent response to trastuzumab. METHODS In the phase II PATRICIA study (ClinicalTrials.gov identifier: NCT02536339 ), patients with HER2-positive MBC with CNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…The phase II PATRICIA trial investigated the efficacy of pertuzumab and high-dose trastuzumab (6 mg/kg weekly) in patients who had experienced progression of BM after CNS radiotherapy but maintained stable extracranial disease. Among the 39 analyzed patients, 11% (95% CI 3-25%) experienced intracranial objective response according to the Response Assessment in Neuro-Oncology Brain Metastases working group (RANO-BM), with a median duration of response (DOR) of 4.6 months [17]. The clinical benefit rate (partial response + complete response + stable disease at 6 months) was 51% [18].…”
Section: Trastuzumab-pertuzumabmentioning
confidence: 99%
“…The phase II PATRICIA trial investigated the efficacy of pertuzumab and high-dose trastuzumab (6 mg/kg weekly) in patients who had experienced progression of BM after CNS radiotherapy but maintained stable extracranial disease. Among the 39 analyzed patients, 11% (95% CI 3-25%) experienced intracranial objective response according to the Response Assessment in Neuro-Oncology Brain Metastases working group (RANO-BM), with a median duration of response (DOR) of 4.6 months [17]. The clinical benefit rate (partial response + complete response + stable disease at 6 months) was 51% [18].…”
Section: Trastuzumab-pertuzumabmentioning
confidence: 99%
“… Untreated, asymptomatic BM or controlled brain disease treated with radiotherapy 398 Total with baseline BM, 126 with measurable BM CNS ORR 21.4% (95% CI, 14.6%-29.6%); clinical benefit rate 42.9% (95% CI, 34.1%-52.0%) High dose trastuzumab and pertuzumab (PATRICIA) Lin et al., J Clin Oncol. 2021 16 HER2-positive advanced breast cancer, CNS metastases, and CNS progression despite prior radiotherapy 39 CNS ORR 11% (95% CI, 3%-25%); clinical benefit rate at 4 months 68%; clinical benefit rate at 6 months 51% Trastuzumab deruxtecan (DESTINY-Breast01, CNS subgroup) Jerusalem et al., J Clin Oncol. 2021 17 HER-positive unresectable or metastatic breast cancer with baseline brain metastases 24 ORR 58.3%, mPFS 18.1 months, CNS response rate per investigators 50% (7 of 14 patients) BM, brain metastases; CI, confidence interval; CNS, central nervous system; HER2, human epidermal growth factor 2; mPFS, median progression free survival; ORR, overall response rate; PFS, progression-free survival; OS, overall survival; ORR-IC, intracranial objective response rate; T-DM1, ado-trastuzumab emtansine.…”
Section: Approach To Treatmentmentioning
confidence: 99%
“…HER2 can also be targeted by monoclonal antibodies that have traditionally been considered to be unable to traverse the BBB. However, preclinical studies have demonstrated that at higher doses, trastuzumab does have BBB penetration [ 44 , 45 ]. This work provided the foundation of the PATRICIA study, evaluating high dose pertuzumab and trastuzumab together in patients with IPM from breast cancer [ 44 ].…”
Section: Her2+ Targeted Therapiesmentioning
confidence: 99%
“…However, preclinical studies have demonstrated that at higher doses, trastuzumab does have BBB penetration [ 44 , 45 ]. This work provided the foundation of the PATRICIA study, evaluating high dose pertuzumab and trastuzumab together in patients with IPM from breast cancer [ 44 ]. This therapy was generally well tolerated and while the primary endpoint was not met due to a modest overall response rate (11%), the clinical benefit rate for these predominantly pretreated patients was 68% at 4 months and 51% at 6 months [ 44 ].…”
Section: Her2+ Targeted Therapiesmentioning
confidence: 99%
See 1 more Smart Citation